The placebo effect in psychiatry: problem or solution? - Huculak, Susan (Journal of medical ethics, 2014)
This opinion piece aims to situate the placebo effect within the field of psychiatric treatment. To accomplish this, the placebo is explored at the centre of an often heated debate between three discrete perspectives: the clinical trial researcher, the placebo researcher and the clinician. Each occupational perspective has its own vested interests and practical concerns that drive how the placebo concepts are negotiated and applied. It is argued that because the trial and placebo researchers typically represent opposing viewpoints, clinicians are generally uncomfortable or even baffled by placebo concepts, and this three-way tension has crucial implications for the field's progress.